2013
DOI: 10.1136/gutjnl-2012-304216
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogens promote tumorigenesis in a mouse model for colitis-associated cancer

Abstract: Our results suggest that oestrogens promote inflammation-associated cancer development by impairing the mucosal response to inflammatory damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
(30 reference statements)
3
26
0
Order By: Relevance
“…One report described a significant reduction in colonic adenomas after OVX, with a reversal to normal numbers by supplementation with 17β-estradiol (22). This tumor-promoting role for estrogens is consistent with the strong estrogen enhancement effect on colonic tumorigenesis associated with inflammation in the mouse (23). This estrogen effect was not reproduced in a subsequent report by the same group, however (24).…”
Section: Discussionsupporting
confidence: 72%
“…One report described a significant reduction in colonic adenomas after OVX, with a reversal to normal numbers by supplementation with 17β-estradiol (22). This tumor-promoting role for estrogens is consistent with the strong estrogen enhancement effect on colonic tumorigenesis associated with inflammation in the mouse (23). This estrogen effect was not reproduced in a subsequent report by the same group, however (24).…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with this, colonic paracellular permeability decreases during the oestrus phase (high levels of estrogen) of the rat when compared to the dioestrus phase (low levels of estrogen) [89]. Although estrogen treatment has been shown to predispose ovariectomized rats to development of ulcerative colitis-induced tumor development [90], most studies to-date have shown that estrogen treatment decreases colonic paracellular permeability and reduces IBD symptom severity [89, 91, 92]. ERβ is the predominant estrogen receptor in the intestinal tract.…”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 91%
“…20,21 Although the impact that p53 has on AOM-induced CRC remains unclear, AOM has a documented relationship with estrogen signaling pathways, and specifically with estrogen receptor alpha (ERα). Estrogen has been demonstrated to promote tumorigenesis in AOM mouse models 22 and other studies have shown a dramatic increase in ERα expression in tumorous tissue after AOM treatment. 23 In this study, we used AOM to induce sporadic colon cancer in genetically engineered mice harboring either the Mdm2 SNP309-G or Mdm2 SNP309-T allele.…”
Section: Introductionmentioning
confidence: 94%